Maritime transport challenges in Latin America's international trade during the period 2010-2023: a literature review - Estrada Liza, Isaac Junior; Flores Poma, Carlos Manuel; Gavilano Esquivel, Luis Diego; Guillen Sanchez, Joshua Felix; Guzman Wong, Bryan Stefano; Cerna Huarachi, Delia Mercedes; Napa Alva, Rosario del Pilar (LACCEI, 2025)
Maritime transport is fundamental in Latin America's international trade, facilitating the movement of goods and strengthening regional economies. However, port infrastructure faces significant challenges that limit its competitiveness in the global market. Problems such as the lack of technological modernization and sustainability have complicated the flow of exports, forcing countries to improve logistics efficiency. Despite progress, Latin American ports still account for a limited fraction of global maritime trade. This study, with a qualitative approach and PRISMA methodology, focuses on examining the challenges faced by maritime transport in Latin America's international trade during the period 2010-2023. The specific objectives cover the analysis of port infrastructure, progress in applied technologies and sustainability challenges in the main ports of Brazil, Chile and Colombia